Predictors of Metabolic Syndrome in University Professors and Rehabilitation Program Development (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article aims to identify the predictors of metabolic syndrome (MetS) among university professors and develop a rehabilitation program to address this issue. Metabolic syndrome, characterized by a cluster of risk factors including obesity, hypertension, dyslipidemia, and insulin resistance, is a significant concern for individuals in sedentary professions. The study examines lifestyle factors, dietary habits, physical activity levels, and stress as potential contributors to MetS in university faculty members. A comprehensive rehabilitation program, including dietary changes, physical activity recommendations, and stress management techniques, is proposed to mitigate the risks associated with MetS. The goal is to improve overall health outcomes and quality of life for academic professionals.